The Use of Temporary Skilled Migration in Australian Organisations - Cameron, Roslyn; Harrison, J. (Emerald Group Publishing Ltd., 2013)
Purpose: The spread of economic global integration in the last 50 years has resulted in the recent emergence of global labour markets. Ageing populations and skill shortages have placed significant pressure upon Australia's economic sustainability and survival in a global economy. The global race for talent has seen the emergence of skilled migration as a key element in Australia's strategy to address major human capital trends and issues and to source pools of talent considered highly skilled or in demand. This paper seeks to address these issues. Design/methodology/approach: This paper draws together research on skilled migration in the Australian context and the factors that explain use of Australia's 457 visa scheme by organisations for attracting and recruiting talent. Data from a survey of members of the Australian Human Resources Institute (n=1,045) is analysed using logistic regression. Findings: The results show that larger, goods producing, organisations with skills shortages are more likely to employ skilled migrants, while not-for-profit and regional organisations are less likely. Sponsorship of 457 visa workers for permanent residency is more likely in larger, regional organisations willing to pay above market rates to fill long‐term vacancies and seeking to attract international skills and knowledge but less likely in public organisations. Research limitations/implications: The study has limitations related to the fact that the sample is limited to Australian members of a human resource professional body. Originality/value: There is very little literature on the use of temporary skilled migration by organisations from a HRM perspective. The findings shed light upon the extent of employer‐sponsored temporary skilled migration as a talent sourcing strategy in a range of industries and organisations across Australia.